Peripheral Arterial Stiffness Increases the Risk of Progression of Renal Disease in Type 2 Diabetic Patients - Lim, Tae Hoon; Chung, Seung Min; Lee, Dong Sung; Choi, Se Ra; Moon, Jun Sung; Yoon, Ji Sung; Won, Kyu Chang; Lee, Hyoung Woo (Frontiers in Medicine, 2020)
Aims Our aim was to investigate the effects of peripheral arterial stiffness on the risk of progression of renal disease in patients with type 2 diabetes (T2D). Methods This was a single center, retrospective cohort study. Brachial-ankle pulse wave velocity (baPWV) tests were performed on T2D patients in 2015. Increased arterial stiffness was defined as baPWV of ≥ 1800 cm/sec. We applied criteria for progression of renal disease according to EMPA-REG OUTCOME trial. Results In total, 186 patients were enrolled in the final study. The mean age was 59.1 years and male:female ratio was 1.73:1. Thirteen (7%) patients progressed to renal disease during the average follow-up time of 35.3 months. In particular, the risk of progression to macroalbuminuria was significantly higher in the baPWV ≥ 1800 cm/sec group (HR 6.216, p = 0.020). Individuals with a baPWV of ≥ 1800 cm/sec (when comparisons were adjusted for age, sex, blood pressure, diabetes duration, eGFR, and use of renin-angiotensin system inhibitors) had a significantly higher risk of the progression of renal disease (HR = 8.480, p = 0.014). Conclusion These results suggest that peripheral arterial stiffness (baPWV ≥ 1800 cm/sec) may be a risk factor for the progression of renal disease in T2D patients.